Reference Values for the Pediatric Quality of Life Inventory and the Multidimensional Fatigue Scale in Adolescent Athletes by Sport and Sex. (October 2017) - Snyder Valier, Alison R.; Welch Bacon, Cailee E.; Bay, R. Curtis; Molzen, Eileen; Lam, Kenneth C.; Valovich McLeod, Tamara C.
Background: Effective use of patient-rated outcome measures to facilitate optimal patient care requires an understanding of the reference values of these measures within the population of interest. Little is known about reference values for commonly used patient-rated outcome measures in adolescent athletes. Purpose: To determine reference values for the Pediatric Quality of Life Inventory (PedsQL) and the Multidimensional Fatigue Scale (MFS) in adolescent athletes by sport and sex. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A convenience sample of interscholastic adolescent athletes from 9 sports was used. Participants completed the PedsQL and MFS during one testing session at the start of their sport season. Data were stratified by sport and sex. Dependent variables included the total PedsQL score and the 5 PedsQL subscale scores: physical functioning, psychosocial functioning, emotional functioning, social functioning, and school functioning. Dependent variables for the MFS included 3 subscale scores: general functioning, sleep functioning, and cognitive functioning. Summary statistics were reported for total and subscale scores by sport and sex. Results: Among 3574 males and 1329 female adolescent athletes, the PedsQL scores (100 possible points) generally indicated high levels of health regardless of sport played. Mean PedsQL total and subscales scores ranged from 82.6 to 95.7 for males and 83.9 to 95.2 for females. Mean MFS subscale scores (100 possible points) ranged from 74.2 to 90.9 for males and 72.8 to 87.4 for females. Conclusion: Healthy male and female adolescent athletes reported relatively high levels of health on the PedsQL subscales and total scores regardless of sport; no mean scores were lower than 82.6 points for males or 83.9 points for females. On the MFS, males and females tended to report low effect of general and cognitive fatigue regardless of sport; mean scores were higher than 83.5 points for males and 83.8 points for females. Clinically, athletes who score below the reference values for their sport have poorer health status than average adolescent athletes participating in that sport. Scores below reference values may warrant consideration of early intervention or treatment.